Effect of autogenous and fresh-frozen bone grafts on osteoblast differentiation. Issue 1 (January 2015) - Ferraz, E.P.; Xavier, S.P.; Azevedo, F.G.; de Oliveira, F.S.; Beloti, M.M.; Rosa, A.L.
Abstract Objective Fresh-frozen bone allograft (FFBA) is an alternative to autogenous bone (AB) for reconstructing maxillary bone. Despite the promising clinical results, cell responses to FFBA and AB were not evaluated. Thus, our aim was to compare cells harvested from maxillary reconstructed sites with either AB or FFBA in terms of osteoblast differentiation and to evaluate the effect of culturing cells in contact with FFBA. Methods Cells harvested from three patients submitted to bilateral maxillary reconstruction with AB and FFBA were cultured to evaluate: proliferation, alkaline phosphatase activity, extracellular matrix mineralization and gene expression of osteoblastic markers. The effect of FFBA on osteoblast differentiation was studied by culturing cells harvested from AB in contact with FFBA and evaluating the same parameters. Data were compared using either two-way ANOVA followed by Tukey-b test or Student's t test (p ≤ 0.05). Results Cell proliferation was higher in cultures from AB grafted sites and extracellular matrix mineralization was higher in cultures derived from FFBA grafted sites. The gene expression of alkaline phosphatase, RUNX2, bone sialoprotein and osteocalcin was higher in cells derived from FFBA compared with cells from AB grafted sites. However, the exposure of cells derived from AB to FFBA particles did not have any remarkable effect on osteoblast differentiation. Conclusions These results indicate the higher osteogenic activity of cells derived from FFBA compared with AB reconstructed sites, offering an explanation at cellular level of why FFBA could be a suitable alternative to AB for reconstructing maxillary bone defects.